2017
DOI: 10.1101/238196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shu complex SWS1-SWSAP1 is required for mouse meiotic recombination in concert with the BRCA2 C terminus

Abstract: Homology recognition and DNA-strand invasion ensure faithful homolog pairing and segregation during the first meiotic division 1 . RAD51 and DMC1 recombinases catalyze these steps 2 , with BRCA2 promoting their assembly into nuclear foci 3 . The recently identified human SWS1-SWSAP1 complex, related to the Shu complex in yeast, promotes RAD51 focus formation in cell lines 4,5 . We show here that mouse SWS1-SWSAP1 is critical for meiotic homologous recombination (HR) by promoting the assembly of RAD51 and DMC1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The assembly of both recombinases is ATP-dependent and promoted by several recombination factors in mammals such as ATR, breast cancer 2 protein (BRCA2), TRIP13, the Shu complex SWS1-SWSAP1, and PALB2, etc. (Zelensky, Kanaar, and Wyman, 2014;Abreu et al, 2018;Roig et al, 2010;Pacheco et al, 2018;Felipe-Medina et al, 2020;Zhang et al, 2020b;Zhang et al, 2019a;Widger et al, 2018). Several recent studies identified BRCA2 localizer (MEILB2) and MEILB2's stabilizer (BRME1), both of which form a complex with BRCA2 and function as the recruiter of RAD51 and DMC1 onto ssDNA (Zhang et al, 2019a;2020b;Felipe-Medina et al, 2020).…”
Section: Meiotic Recombinationmentioning
confidence: 99%
“…The assembly of both recombinases is ATP-dependent and promoted by several recombination factors in mammals such as ATR, breast cancer 2 protein (BRCA2), TRIP13, the Shu complex SWS1-SWSAP1, and PALB2, etc. (Zelensky, Kanaar, and Wyman, 2014;Abreu et al, 2018;Roig et al, 2010;Pacheco et al, 2018;Felipe-Medina et al, 2020;Zhang et al, 2020b;Zhang et al, 2019a;Widger et al, 2018). Several recent studies identified BRCA2 localizer (MEILB2) and MEILB2's stabilizer (BRME1), both of which form a complex with BRCA2 and function as the recruiter of RAD51 and DMC1 onto ssDNA (Zhang et al, 2019a;2020b;Felipe-Medina et al, 2020).…”
Section: Meiotic Recombinationmentioning
confidence: 99%